Sperm motility is the main problem for honeybee's reproduction both in natural and in artificial insemination. Sperm produced only by sexually mature drone. Drone with high semen volumes can be seen by the external morphology like hairy in back and the existence of yellow stripes on their black abdomen. Semen samples were collected from the drone by the massage technique; these consist of massaging the abdomen of drone. This massage proceeded until penis and semen cream to yellow color, was - Lea Tarliyah; Arief Boediono; Djoko Walujo (Media Veteriner, 1999)
Sperm motility is the main problem for honeybee's reproduction both in natural and in artificial insemination. Sperm produced only by sexually mature drone. Drone with high semen volumes can be seen by the external morphology like hairy in back and the existence of yellow stripes on their black abdomen. Semen samples were collected from the drone by the massage technique; these consist of massaging the abdomen of drone. This massage proceeded until penis and semen cream to yellow color, was produced. Semen taken out with spuit (3 ml) that contain a modification dilution media called